Survival strategies of gill net fishermen households in North Bontang District, Bontang City, East Kalimantan - Song, Veronika; Syafril, Muhammad; Darmansyah, Oon (Faculty of Fisheries and Marine Science, Mulawarman University, 2025)
This study aims to determine the socio-economic conditions and survival strategies of gillnet fishermen households in maintaining their lives. The research was conducted for 11 months from July to May 2024 in Bontang Kuala Village, North Bontang District, Bontang City. The method used in sampling fishermen is simple random sampling with a total of 34 respondents. The analysis method uses qualitative descriptive analysis. The results showed that the socio-economic conditions of the majority of gill net fishermen were productive age 53-59 years, the average education level was elementary school 26 people, fishermen's income ranged from IDR 420,000 - IDR 3,000,000 per month with an average per fisherman IDR 2,031,470. Their status is owner fishermen with fishing fleets in the form of boats with no engine, boats with ketinting engines and boats or boats with dompeng engines. Fishermen's residences are generally semi-permanent houses with good physical conditions and the land ownership status of the house building is Hak Guna Bagunan (HGB). Fishermen's survival strategies are carried out in three ways, namely, active strategies by doing side jobs, optimising the role of family members (wife and children) and increasing working hours at sea. Passive strategies, reducing the cost of food, clothing, education and setting aside money or saving money from fish sales. Network strategies, making loans through horizontal social networks (family) and vertical social networks (collectors), as well as economic or financial institutions, such as cooperatives, banks, People's Business Credit (PBC) through fisheries organisations and utilising poverty programs.